2011
DOI: 10.1074/jbc.m111.233700
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Nesprins and Sun Proteins at the Nuclear Envelope Is Critical for Force Transmission between the Nucleus and Cytoskeleton

Abstract: Maintaining physical connections between the nucleus and the cytoskeleton is important for many cellular processes that require coordinated movement and positioning of the nucleus. Nucleo-cytoskeletal coupling is also necessary to transmit extracellular mechanical stimuli across the cytoskeleton to the nucleus, where they may initiate mechanotransduction events. The LINC (Linker of Nucleoskeleton and Cytoskeleton) complex, formed by the interaction of nesprins and SUN proteins at the nuclear envelope, can bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
535
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 468 publications
(557 citation statements)
references
References 36 publications
19
535
0
3
Order By: Relevance
“…These interactions are mediated by the nesprin Klarsicht, ANC-1, Syne Homology (KASH) domain and can be uncoupled by the overexpression of a construct encoding the KASH domain (31). For this reason, we overexpressed a GFP-fused KASH domain of mouse nesprin 1α (31) and showed that such overexpression, indeed, removed nesprin 2 from the nuclear envelope (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These interactions are mediated by the nesprin Klarsicht, ANC-1, Syne Homology (KASH) domain and can be uncoupled by the overexpression of a construct encoding the KASH domain (31). For this reason, we overexpressed a GFP-fused KASH domain of mouse nesprin 1α (31) and showed that such overexpression, indeed, removed nesprin 2 from the nuclear envelope (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During neuronal migration, the nucleus is repeatedly pulled by microtubule-associated cytoplasmic motors toward the centrosome near the leading edge of the cell (nucleokinesis) (38,39). The microtubule network almost certainly binds to the cell nucleus through interactions with LINC complex (involving SUN1/2 and Nesprin-1/2) (40,41), and this same complex likely binds to the nuclear lamina (40,42). We suspect that the dumbbell-shaped nuclei and naked chromatin in migrating Lmnb1 CS/CS neurons are a consequence of weakened interactions between the nuclear lamina and the inner nuclear membrane (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Actin is physically linked to the nucleus via nesprin, which is a component of the LINC complex (49). To understand whether this physical link is necessary for nuclear deformability, cells were transfected with dominant negative (DN)-KASH fused with GFP, which displaces the endogenous nesprin from the nuclear envelope to the endoplasmic reticulum, thereby disrupting the LINC complex (50). These cells were then cultured on CI fibronectin micropatterns, and time lapse imaging of H2B-mRFP labeled nuclei was performed in cells expressing DN-KASH GFP ( Fig.…”
Section: Linc Complex and Microtubules Affect Amplitude Of Nuclear Areamentioning
confidence: 99%